Center of gravity height and number of falls in active and sedentary older adults - Fernanda Veruska Narciso; Sílvio Soares Santos; Fernanda Ferreira; Vanessa Silva Lemos; Mário Antonio Barauna; Nádia Carla Cheik; Roberto Sérgio de Tavares Canto (Universidade Federal de Santa Catarina, 2010)
Older adults present changes in energy metabolism that result in an increase of body fat and a decrease of muscle mass and height, leading to alterations in the position of the center of gravity (CG) and consequent falls. The objective of the present study was to compare the percent CG height and the number of falls (NF) over the last 12 months between active and sedentary older adults and to correlate them with anthropometric variables (body weight, height and BMI). The sample consisted of 102 men and women ranging in age from 60 to 84 years, including 64 active and 38 sedentary subjects. Anthropometric variables, NF, level of physical activity of sedentary subjects, and percent CG height were evaluated and the mean and standard deviation were calculated. Correlations between variables were estimated using Pearson's correlation coefficient. The percent CG height was 57.54 ± 2.57% in active subjects and 57.47 ± 1.94% in sedentary subjects. No significant correlations were observed between percent CG height and anthropometric variables or NF in either group. In conclusion, older adults present a CG above the physiological value (55%). No significant association was observed between percent CG height, anthropometric variables and NF.